Government Expenditure and Economic Growth of Nepal - Dhungel, Bashu Dev (Humanities and Social Sciences Journal, 2022)
This paper investigates the effects of public spending on Nepalese GDP growth from the fiscal year 1990/91 to 2019/20. This study has applied Stationary Test along with ordinary least square method to investigate the role of explanatory variables on GDP growth of Nepal. Agriculture, education, health and transportation and communication are all included in government spending. All explanatory variables have made favorable effect on Nepal’s GDP growth. The multivariate regression analysis confirms that community expenditure in health sector as well as education sector leads to uplift the human capital which have ultimately positive influence on theeconomic growth of the country.